A global atmospheric model of meteoric iron. Issue 16 (29th August 2013) - Feng, Wuhu; Marsh, Daniel R.; Chipperfield, Martyn P.; Janches, Diego; Höffner, Josef; Yi, Fan; Plane, John M. C.
Abstract : [1] The first global model of meteoric iron in the atmosphere (WACCM‐Fe) has been developed by combining three components: the Whole Atmosphere Community Climate Model (WACCM), a description of the neutral and ion‐molecule chemistry of iron in the mesosphere and lower thermosphere (MLT), and a treatment of the injection of meteoric constituents into the atmosphere. The iron chemistry treats seven neutral and four ionized iron containing species with 30 neutral and ion‐molecule reactions. The meteoric input function (MIF), which describes the injection of Fe as a function of height, latitude, and day, is precalculated from an astronomical model coupled to a chemical meteoric ablation model (CABMOD). This newly developed WACCM‐Fe model has been evaluated against a number of available ground‐based lidar observations and performs well in simulating the mesospheric atomic Fe layer. The model reproduces the strong positive correlation of temperature and Fe density around the Fe layer peak and the large anticorrelation around 100 km. The diurnal tide has a significant effect in the middle of the layer, and the model also captures well the observed seasonal variations. However, the model overestimates the peak Fe + concentration compared with the limited rocket‐borne mass spectrometer data available, although good agreement on the ion layer underside can be obtained by adjusting the rate coefficients for dissociative recombination of Fe‐molecular ions with electrons. Sensitivity experiments with the same chemistry in a 1‐D model are used to highlight significant remaining uncertainties in reaction rate coefficients, and to explore the dependence of the total Fe abundance on the MIF and rate of vertical transport. Key Points: The first global atmospheric meteoric iron model. This study connects the astronomy and atmospheric sciences Understanding the processes controlling the Fe layer